Systematic Literature Review: MATHEMATICAL CONNECTIONS THROUGH PROBLEM-BASED LEARNING IN TERMS OF ADVERSITY QUOTIENT - SUPONO, LILIK; Agoestanto, Arief (JME (Journal of Mathematics Education), 2023)
Mathematical connection is a skill needed to understand mathematical concepts and relate them to formulas taught, once taught, applied in other subjects, and also applied to the real world. Every student has differences in terms of mathematical connection ability. This is known as the Adversity Quotient (AQ). AQ is divided into three groups namely Climbers, Campers, and Quitters. Apart from the AQ review, there is an appropriate learning model to be used in improving students' mathematical connections, namely the Problem Based Learning (PBL) model. PBL is a learning model related to everyday problems. The purpose of this study is to (1) determine the effect of AQ on mathematical connection skills in the PBL learning model (2) determine the influence of AQ on mathematical connection skills.The discussion in this article uses the SLR (System Literature review) method searched from Google Scholar, Scimago Journal Rank, and Publish or Perish from 2013 to 2023. The results of this study get 22 relevant articles. Of the 24 articles studied, 14 articles concluded that mathematical connections are appropriate to use in PBL learning models and 8 articles concluded that the effect of AQ on students' mathematical connections is proportional or directly proportional. Students with a good AQ will have good math connections.